Potensi Stand Up Comedy pada Kanal Youtube dalam Model Pembelajaran Sinektik: Perspektif Guru Sekolah Dasar - Sandra Tri Febriani; Nazurty Nazurty; Irma Suryani (Journal of Society Counseling, 2026)
Persistent constraints in idea generation continue to characterize narrative writing among sixth-grade elementary students, whose cognitive development remains closely tied to concrete and experiential stimuli. The integration of stand-up comedy content from YouTube into a synectics-based learning framework emerges as a pedagogical alternative that bridges affective engagement and cognitive activation. The underlying assumption positions humor-driven narratives and analogical thinking as complementary mechanisms for stimulating creative expression in writing. A qualitative descriptive-exploratory approach was employed, centering on in-depth semi-structured interviews with primary school teachers. The analytical process followed a thematic orientation, capturing how teachers interpret the relevance, feasibility, and pedagogical implications of the proposed model within classroom practice. The findings reveal a consistent recognition of contextual relevance and motivational value, particularly in facilitating idea generation through relatable and humorous narratives. At the same time, concerns regarding classroom control, content appropriateness, and instructional alignment indicate that implementation is neither automatic nor neutral. The significance of these findings lies in repositioning instructional innovation as a teacher-mediated process, in which effectiveness depends less on the model itself than on the pedagogical judgment that shapes its adaptation and enactment.